Spatiotemporal successions of shrimp gut microbial colonization: high consistency despite distinct species pool - Xiong, Jinbo; Xuan, Lixia; Yu, Weina; Zhu, Jinyong; Qiu, Qiongfen; Chen, Jiong (Environmental microbiology, 2019)
Summary Aquatic animals encounter suites of novel planktonic microbes during their development. Although hosts have been shown to exert strong selection on their gut microbiota from surrounding environment, to what extent and the generality that the gut microbiota and the underlying ecological processes are affected by biotic and abiotic variations are largely unclear. Here, these concerns were explored by coupling spatiotemporal data on gut and rearing water bacterial communities with environmental variables over shrimp life stages at spatially distant locations. Shrimp gut microbiotas significantly changed mirroring their development, as evidenced by gut bacterial signatures of shrimp life stage contributing 95.5% stratification accuracy. Shrimp sourced little (2.6%–15.8%) of their gut microbiota from their rearing water. This microbial resistance was reflected by weak compositional differences between shrimp farming spatially distinct locations where species pools were distinct. Consistently, the assembly of shrimp gut microbiota was not adequately explained by the rearing water variables and bacterial community, but rather by host‐age‐associated biotic features. The successions of shrimp gut microbiota were droved by replacement (βsim), rather than by nestedness (βnes), while those of bacterioplankton communities were equally governed by replacement and nestedness. Our study highlights how shrimp gut bacterial community assembly is coupled to their development, rearing species pool, and that the successional pattern of host‐associated communities is differed from that of free‐living bacteria.